Some examples of lexicographic order algorithms and some open combinatorial problems (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1997)
A general reasoning based on the lexicographic order is studied. It helps to create algorithms for generation of sets of words having certain natural and good properties. Several examples are considered and the performance of the proposed algorithms is calculated. An open combinatorial problem regarding the set of partitions arises.